Attentional and Emotional Mechanisms of Pain Processing and Their Related Factors: A Structural Equations Approach - Claudia Huber; Miriam Kunz; Cordula Artelt; Stefan Lautenbacher (Pain Research and Management, 2010)
BACKGROUND/OBJECTIVE: It is known that maladaptive attentional and emotional mechanisms of pain processing – as indicated by constructs such as pain hypervigilance, pain-related anxiety and pain catastrophizing – play an important role in the development and maintenance of chronic pain conditions. However, little is known to date about the potential risk factors for these forms of maladaptive processing. The aim of the present study was to shed more light on this issue. A very comprehensive set of predictor variables was examined in healthy pain-free subjects.